Enhancement of glycolysis by inhibition of oxygen‐sensing prolyl hydroxylases protects alveolar epithelial cells from acute lung injury. Issue 4 (5th January 2018) - Tojo, Kentaro; Tamada, Nao; Nagamine, Yusuke; Yazawa, Takuya; Ota, Shuhei; Goto, Takahisa
Abstract : Cellular bioenergetic failure caused by mitochondrial dysfunction is a key process of alveolar epithelial injury during acute respiratory distress syndrome (ARDS). Prolyl hydroxylases (PHDs) act as cellular oxygen sensors, and their inhibition activates hypoxia‐inducible factor (HIF), resulting in enhanced cellular glycolytic activity, which could compensate for impaired mitochondrial function and protect alveolar epithelial cells from ARDS. Here, we evaluated the effects of pharmacological PHD inhibition with dimethyloxalylglycine (DMOG) on alveolar epithelial cell injury using in vitro and in vivo ARDS models. We established an in vitro model of alveolar epithelial injury mimicking ARDS by adding isolated neutrophils and LPS to cultured MLE12 alveolar epithelial cells. DMOG treatment protected MLE12 cells from neutrophil‐LPS‐induced ATP decline and cell death. Knockdown of HIF‐1α or inhibition of glycolysis abolished the protective effect of DMOG, suggesting that it was exerted by HIF‐1‐dependent enhancement of glycolysis. Additionally, intratracheal DMOG administration to mice protected the alveolar epithelial barrier and improved arterial oxygenation, preventing ATP decline during LPS‐induced lung injury. In summary, enhancement of glycolysis by PHD inhibition is a potential therapeutic approach for ARDS, protecting alveolar epithelial cells from bioenergetic failure and cell death.— Tojo, K., Tamada, N., Nagamine, Y., Yazawa, T., Ota, S., Goto, T. Enhancement of glycolysis by inhibition of oxygen‐sensing prolyl hydroxylases protects alveolar epithelial cells from acute lung injury. FASEB J. 32, 2258–2268 (2018). www.fasebj.org